Pengislahan masyarakat Melayu : perbincangan al-Imam (1906-1908) - Abdul Aziz Mat Ton (Dewan Bahasa dan Pustaka, 2006)
Historical analysis of al-Imam magazine and its contribution to economic, political, and educational development of the Malay world, 1906-1908